Contribuições da epistemologia genética para a construção do conhecimento na educação infantil - Lepre, Rita Melissa [UNESP]; Garms, Gilza Zauhy [UNESP]; Seixlack, Ana Lúcia Baldo [UNESP]; Thimóteo, Rosemeire [UNESP] (My University, 2012)
The kindergarten has as main objective the development of the child from zero to five years in their physical, emotional, cognitive and social domains. This is also the goal of the Centers for Children Living from the Universidade Estadual Paulista (UNESP) that caters to children of teachers, technical and administrative staff and students. In this work we report some of the action of the Technical Commission of the CCIs with reflections on the construction of children's knowledge through observations of the CCIs in different campuses of Unesp, conducted through technical visits. As a theoretical contribution we adopt the Genetic Epistemology of Jean Piaget. Partial results show that, although there are efforts to understand and assist the process of constructing knowledge of children, many challenges remain to be overcome in the realization of an excellent service to children.

L'éducation préscolaire a pour objectif central le développement des enfants de zéro à cinq ans dans leur aspects physique, affectif, cognitif et social. C'est également l'objectif des Centres Sociaux d'Enfants (CCI) de “l’Universidade Estadual Paulista” (UNESP) qui s'adresse aux enfants d'enseignants, de personnel technique et administratif et les étudiants. Dans cet article nous présentons une partie du travail de la Commission Technique de la CCI (Prad/Reitoria) avec des réflexions sur la construction de la connaissance des enfants grâce à des observations faites dans les CCI des différents Campus de UNESP, à partir des visites techniques. Comme apport théorique, nous adoptons l'Épistémologie Génétique de Jean Piaget. Les résultats partiels montrent que, bien qu'il existe des efforts pour comprendre et aider le processus de construction des connaissances des jeunes enfants, les défis restent à surmonter dans la réalisation d'un excellent service aux enfants.

A Educação Infantil tem como objetivo central o desenvolvimento integral da criança de zero a cinco anos em seus aspectos físico, afetivo, cognitivo e social. Esse é, também, o objetivo dos Centros de Convivência Infantil da Universidade Estadual Paulista (Unesp) que atende a filhos de docentes, técnico-administrativos e discentes. Neste artigo relataremos uma parte do trabalho da Comissão Técnica dos CCIs (Prad/Reitoria) com reflexões acerca da construção do conhecimento das crianças por meio de observações realizadas nos CCIs dos diferentes campi da Unesp, quando realizadas as visitas técnicas. Como aporte teórico adotamos a Epistemologia Genética de Jean Piaget. Os resultados parciais revelam que, ainda que haja esforços no sentido de entender e auxiliar o processo de construção do conhecimento das crianças pequenas, permanecem desafios a serem superados na efetivação de um atendimento de excelência às crianças.
Contributions of epistemology genetic to the construction of knowledge in early childhood education
Contributions d’épistémologie génétique pour la Construction des connaissances sur l’éducation préscolaire
Keywords: Building knowledge; Child development; Early childhood education; Genetic epistemology; Construction des connaissances; Développement de l'Enfant; Éducation Préscolaire; Épistémologie génétique; Construção do conhecimento; Desenvolvimento infantil; Educação infantil; Epistemologia genética